THE CULTURAL NON-HUMAN ANIMAL ANALYSING ITALO CALVINO’S ITALIAN FAIRY TALES WITH ZOOSEMIOTICS - BUSCEMI, Francesco (Studia Universitatis Babeș-Bolyai Philologia, 2022)
The Cultural Non-human Animal. Analysing Italo Calvino’s Italian Fairy Tales with Zoosemiotics. This article analyses traditional Italian fairy tales retold by Italo Calvino in 1956 and their relationships to nature and culture. Zoosemiotics, a branch of both semiotics and animal studies, argues that nature and culture are not separated and in contrast and that, instead, culture is a limited part of nature. This conceptual change envisions different relationships between humans and animals as well as more broadly the end of animal anthropomorphism. Methodologically, the article applies a zoosemiotic analysis to the Italian fairy tales retold by Calvino. The article concludes that some animals in the fairy tales are still anchored to the old view while others move towards the cultural terrain, showing cultural attitudes and inhabiting a cultural area usually reserved for human animals. This shift leads to an inverted semiotic destiny of humans and animals in fairy tales: while animals are traditionally represented as symbols, Calvino’s rewriting turns them into icons, representing only themselves, marked by a neat individuality and independence from their species; while humans are, conversely, usually represented as icons, Calvino’s stories turn them into symbols, such as ingratitude or jealousy. The article shows the usefulness of zoosemiotics and nature/culture in analysing non human-animals in fairy tales and adds to earlier studies considering non-human animals in Calvino’s fairy tales as an epitome of Anthropocene. Article history: Received 2 February 2022; Revised 5 May 2022; Accepted 24 May 2022; Available online 30 June 2022; Available print 30 June 2022. REZUMAT. Animalul cultural non-uman. O analiză a poveștilor lui Italo Calvino cu ajutorul zoosemioticii. Articolul de față analizează povești italiene tradiționale repovestite de către Italo Calvino în 1956, precum și relația lor cu natura și cultura. Zoosemiotica, o ramură atât a semioticii cât și a studiilor despre animale, argumentează că natura și cultura nu sunt separate și nu se află în contrast, ci că, dimpotrivă, cultura este o parte limitată a naturii. Această schimbare conceptuală preconizează relații diferite între oameni și animale, precum și, în sens mai general, sfârșitul antropomorfismului animalelor. Metodologic, articolul aplică o analiză zoosemiotică poveștilor italiene repovestite de Calvino. Articolul conchide că anumite povești cu animale sunt încă ancorate într-o viziune mai veche, în timp ce altele se deplasează către un teren cultural, demonstrând atitudini culturale și populând aria culturală rezervată de obicei animalelor umane. Această schimbare conduce la un destin semiotic inversat al oamenilor și animalelor în povești: în vreme ce animalele sunt în mod tradițional reprezentate ca simboluri, rescrierea lui Calvino le transformă în icon-uri, ele reprezentându-se doar pe sine, marcate de o individualitate și de o independență distincte față de specia lor, în timp ce oamenii, de obicei reprezentați ca icon-uri, sunt transformați în povestirile lui Calvino în simboluri, de pildă ale ingratitudinii ori geloziei. Articolul arată utilitatea zoosemioticii și binomului natură/cultură în analiza animalelor non-umane în povești, și aduce contribuții la studiile anterioare despre animalele non-umane în poveștile lui Calvino ca întruchipare a Antropocenului. Cuvinte-cheie: studii despre animale, povești, Italo Calvino, zoosemiotică, natură și cultură, antropomorfism, Motanul încălțat